To complete the polynomial equation, we need to perform the subtraction of the second polynomial from the first polynomial.
Given:
- First polynomial: \( 9x^2 + bx + 13 \)
- Second polynomial: \( -2x^2 + 12x + c \)
- Resulting polynomial after subtraction: \( dx^2 + 5x + 2 \)
The subtraction can be expressed as follows:
\[ (9x^2 + bx + 13) - (-2x^2 + 12x + c) = dx^2 + 5x + 2 \]
Simplifying the left side gives:
\[ 9x^2 + bx + 13 + 2x^2 - 12x - c = dx^2 + 5x + 2 \] \[ (9 + 2)x^2 + (b - 12)x + (13 - c) = dx^2 + 5x + 2 \]
Now, we can equate the coefficients for each corresponding power of \(x\):
-
For \(x^2\): \[ 9 + 2 = d \Rightarrow d = 11 \]
-
For \(x\): \[ b - 12 = 5 \Rightarrow b = 17 \]
-
For the constant term: \[ 13 - c = 2 \Rightarrow c = 11 \]
Putting all the values together, we have:
- \(b = 17\)
- \(c = 11\)
- \(d = 11\)
So, the completed polynomial equation with the blanks filled in is:
\[ 9x^2 + 17x + 13
- 2x^2 + 12x + 11 = 11x^2 + 5x + 2 \]